Characteristics of Helicobacter Pylori-Related Dyspepsia and Dysglycemia: A Review - Nasrat, Abdullah M; Nasrat, Salwa AM; Nasrat, Randa M; Nasrat, Mohammad M (Disease and Health: Research Developments Vol. 3, 2025)
H. pylori colonized the stomach since immemorial time as if both the stomach wall and the bacterium used to live together in peace harmless to each other. In many cases of newly discovered diabetes associated with frank history of H. pylori dyspepsia, the diabetic condition has been successfully and permanently corrected by mere eradication of colonic H. pylori strains. The world literature is considering that the world’s burden of diabetes is on the account of type II diabetes although the newly discovered diabetic condition has been successfully and readily corrected permanently in many patients. Traditional risk rules do not appear fully sufficient to explain the dramatic spread of diabetes mellitus all over the world; this could further indicate that traditional measures employed to control the problem could never be adequate or decisive. Most diabetic patients in the world are inadequately controlled in spite of regular follow-up of medications and strict carefulness about their style of life; this could also indicate the presence of a missed underlying etiologic pathological error. It has been lately emphasized that the world’s burden of diabetes is not on the account of type II diabetes but on stress diabetes due to toxic pancreatitis caused by the accumulation of potential toxins in the colon. The aim of the study is to evaluate the characteristics of Helicobacter pylori-related Dyspepsia and Helicobacter pylori-induced Dysglycemia.